PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS PERMULAAN DI KELAS II SD - Puadi, Nurul; Suhandi Saputra, Dudu; Damayanti, Indani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low early writing skills of elementary school students, as indicated by difficulties in using capital letters, punctuation marks, letter completeness, handwriting neatness, and constructing simple sentences. The purpose of this study was to determine the effect of the Problem Based Learning (PBL) model on the early writing skills of second-grade students at SDN Jatipamor 1. This study employed a quantitative approach using a quasi-experimental research method with a nonequivalent control group design. The research sample consisted of 24 students in Class II B as the experimental group and 20 students in Class II A as the control group, selected through purposive sampling. The research instrument was an early writing skills test administered through pretests and posttests. Data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and the Independent Sample t-Test. The results showed that the mean score of the experimental group increased from 57.97 on the pretest to 75.34 on the posttest, while the control group increased from 52.32 to 56.19. The Independent Sample t-Test revealed a significance value (2-tailed) of < 0.001, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the Problem-Based Learning model had a significant effect on the early writing skills of second-grade students at SDN Jatipamor 1. The Problem-Based Learning model can be considered an effective instructional approach for improving elementary school students' early writing skills.